2001
DOI: 10.1097/00000658-200110000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Curative Resection for Esophageal Adenocarcinoma

Abstract: Long-term survival from adenocarcinoma of the esophagus can be achieved in more than half the patients who undergo en bloc resection. One third of patients with lymph node involvement survived 5 years. Local control is excellent after en bloc resection. The extent of disease associated with tumors confined to the mucosa and submucosa provides justification for more limited and less morbid resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
211
0
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(234 citation statements)
references
References 37 publications
13
211
0
10
Order By: Relevance
“…The first approach is based on studies that showed and 24 months (95% CI: 18-30 months) [84]. The second school advocates an optimum cut off point, above which prognosis significantly falls [11,15,17,22,71], of 4 lymph nodes (reported range: 3-7 involved lymph nodes) [13, 14, 41, 54, 57, 71, 79, 87, 94 95]. When comparing patients with greater than four involved lymph nodes to those with four or less involved lymph nodes, the risk of developing recurrent disease rises from 45% to 82% and the 5-year survival is significantly reduced [13,22,71,87,89].…”
Section: Prognostic Implications: Number Of Positive Lymph Nodesmentioning
confidence: 99%
See 3 more Smart Citations
“…The first approach is based on studies that showed and 24 months (95% CI: 18-30 months) [84]. The second school advocates an optimum cut off point, above which prognosis significantly falls [11,15,17,22,71], of 4 lymph nodes (reported range: 3-7 involved lymph nodes) [13, 14, 41, 54, 57, 71, 79, 87, 94 95]. When comparing patients with greater than four involved lymph nodes to those with four or less involved lymph nodes, the risk of developing recurrent disease rises from 45% to 82% and the 5-year survival is significantly reduced [13,22,71,87,89].…”
Section: Prognostic Implications: Number Of Positive Lymph Nodesmentioning
confidence: 99%
“…Lymph node metastases occur rapidly and extensively involving both the regional and systemic lymph nodes via the thoracic duct [54,79]. Studies have shown that up to 35% of T1b tumours and 78-85% of T3 tumours have lymph node metastases [11,18].…”
Section: Location Of Positive Lymph Nodesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of surgical techniques, many advances have been applied to the surgery of esophageal cancer in the past decade [7,8]. Although lower rate of mortality has always been reported [9][10][11], the postoperative complications are proven to be frequently common, which included anastomotic leakage and stricture. Among the factors leading to the higher mortality, anastomotic leakage plays an essential role, with the rate ranging from 0 to 41 % [12].…”
Section: Introductionmentioning
confidence: 99%